A novel method for cyanide quantification in human whole blood using ion chromatography with amperometric detection and its application to cyanide intoxication cases. Issue 1 (29th September 2021) - Sim, Juhyun; Kim, Minyoul; Kim, Suncheun; Yang, Wonkyung
Abstract: Cyanide is a highly toxic agent that has been frequently used for suicide in South Korea. It is also used in various industrial fields, such as metal plating, in which many accidental cyanide intoxications have occurred. To overcome the disadvantages of conventional cyanide analysis methods, a simple and fast method for the analysis of cyanide in whole blood using ion chromatography (IC) with amperometric detection was developed in this study. Whole blood samples were deproteinized, diluted, and analyzed using an IC–amperometric detection system. The limits of detection and quantitation were 0.1 and 0.2 mg/L, respectively. The method showed good linearity in the range of 0.2 to 50 mg/L with R 2  > 0.99. The intra‐ and inter‐assay precision and accuracy values were <10%. The established method was successfully applied to analyze whole blood samples from three cyanide intoxication cases.